2009
DOI: 10.1590/s0104-42302009000200011
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência da rubéola na população urbana e rural de Guaratinguetá

Abstract: com diferença significativa na proporção de soropositivos pela faixa etária ( p < 0,001 ). A variação de intensidade da resposta anticórpica foi calculada e os resultados mostram que há diferença significativa (p = 0,002) entre as médias das três faixas etárias estudadas. Em relação à área rural e urbana, a média da relação DO/CO para cada faixa etária, observa-se que há uma tendência significativa de médias menores na zona rural. O mesmo ocorre quando são calculadas as proporções de soropositivos. CONCLUSÃO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Although our study agrees with some studies such as by Karakoc et al ( 23 ) that show no significant association of the outcome with economic status, low socio-economic status has also been seen to be associated with risk of rubella infection in other studies ( 24 , 25 ). Our study agrees with authors such as Kombich et al ( 25 ) that found no association between education and rubella infection.…”
Section: Discussionsupporting
confidence: 91%
“…Although our study agrees with some studies such as by Karakoc et al ( 23 ) that show no significant association of the outcome with economic status, low socio-economic status has also been seen to be associated with risk of rubella infection in other studies ( 24 , 25 ). Our study agrees with authors such as Kombich et al ( 25 ) that found no association between education and rubella infection.…”
Section: Discussionsupporting
confidence: 91%